Penerapan Rancangan Faktorial Pada Uji Pengaruh Pupuk Organik Pelet dari Limbah Perkotaan Terhadap Kandungan Gizi Sayuran Bayam (Amaranthus hybridus L): Application of Factorial Design in Test of the Effect of Organic Fertilizer Pellets from Urban Waste on the Nutritional Content of Spinach Vegetables (Amaranthus hybridus L) - Haryanta, Dwi; Rejeki, Fungki Sri (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
Factorial experimental designs involve more than one factor and what needs to be tested is the interaction between treatment factors in addition to the effects of each treatment factor itself. This study aims (a) to consider graphical line drawings as a reference for formulating conclusions that there is an interaction between the two treatment factors, and (b) to examine and follow up on the results of the analysis of variance in factorial experiments which conclude that the interaction between the two factors is significant, not to ignore the possibility of single factor variance dominating. . The research refers to the research data